2007
DOI: 10.1002/j.2055-2335.2007.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Specialised Compounding—Practices and Opinions of Australian Community Pharmacists

Abstract: Background: Anecdotal reports of the increase in dispensing of compounded products have resulted in a review of pharmacy compounding by regulatory authorities. However, little is known about the compounding practices of community pharmacists. Aim: To investigate the extent and nature of compounding in community pharmacies, to assess the differences between specialised and non-specialised compounding practices and to evaluate pharmacists' attitudes to compounding as a specialty. Method: A 42-item self-completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…By this we mean extemporaneous preparation of medicines over and above routine practice. Australian researchers found that between 6 and 10% of Australian pharmacies offer compounding as a specialised or enhanced service [62][63][64]. Although research on the characteristics of specialised compounding pharmacies is sparse, a study conducted by the authors uncovered differences in organisational aspects of ''general'' (non-specialist) pharmacies and specialised compounding pharmacies.…”
Section: Compounding As a Reprofessionalisation Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…By this we mean extemporaneous preparation of medicines over and above routine practice. Australian researchers found that between 6 and 10% of Australian pharmacies offer compounding as a specialised or enhanced service [62][63][64]. Although research on the characteristics of specialised compounding pharmacies is sparse, a study conducted by the authors uncovered differences in organisational aspects of ''general'' (non-specialist) pharmacies and specialised compounding pharmacies.…”
Section: Compounding As a Reprofessionalisation Strategymentioning
confidence: 97%
“…There is evidence that compounding is increasingly being offered in the US and Australia as a specialised or enhanced community pharmacy service [60][61][62][63]. By this we mean extemporaneous preparation of medicines over and above routine practice.…”
Section: Compounding As a Reprofessionalisation Strategymentioning
confidence: 99%
“…Previous mailing surveys conducted among the Australian pharmacies or pharmacists found that the response rates were around 40-60% [36][37][38][39]. Interestingly, all the studies involved self-administered questionnaires which can be completed in a short space of time [36][37][38][39].…”
Section: Study Limitationmentioning
confidence: 98%
“…In Australia, pharmacists not specialising in compounding services still compound on average three products per week and the 10% of pharmacists specialising in compounding average 25 products per week, just under 1% of all prescriptions. 4 In Australia, prescription medicines are registered in the Australian Register of Therapeutic Goods under the Therapeutic Goods Act 1989 ('the Act'). Regulations under the Act (Therapeutic Goods (Manufacturing Principles) Determination no.…”
mentioning
confidence: 99%
“…In Australia, both complexity and scale of compounding are increasing. 4 A physician usually focuses on prescription medicines, but there are other products relevant to our patients. Complementary and alternative medicines are products used with therapeutic intent and are a multimillion dollar industry in Australasia.…”
mentioning
confidence: 99%